AN APPLICATION OF A LASER DRILLING TECHNIQUE TO FIR AND SPRUCE WOOD SPECIMENS TO IMPROVE THEIR PERMEABILITY (Innovation in Woodworking Industry and Engineering design, 2026)
In this work, the application of a laser drilling technique on fir (Abies borisii regis) and spruce (Picea excelsa) wood and a new approach of improvement the wood permeability is investigated. This technique is focusing on increasing the permeability of wood after surface drilling by a high power laser source. The research was involving the establishment of an effective drilling pattern protocol, which will not substantially affect the mechanical strength of wood and to improve its permeability. All lateral surfaces of the wood specimens, 2 × 2 cm in cross section and 34 cm long, were drilled by laser to a depth of 4 mm (1/5 of specimen thickness) with two drilling patterns (distance between holes 10 × 10 mm and 10 × 20 mm). Preliminary results showed that laser drilling is a promising method for improvement of wood permeability without significant effect on its mechanical strength, and this is very important for an effective treatment of the refractory to impregnation fir and spruce wood.